Small molecular sugars effect on the pasting and retrogradation of Mesona chinensis polysaccharide/starch complexes - Su, Yu‐Bin; Zhang, Jiawei; Huang, Kaijiao; Xie, Nengzhong (International journal of food science & technology, 2024)
Summary Small molecular sugars have gained substantial attention as common food additives for anti‐retrogradation of starch. However, the effect of small molecular sugars on the pasting and retrogradation behaviours of starchy foods with complex components is different from that of native starch owing to the interaction between different components. In this study, the pasting and retrogradation behaviours of Mesona chinensis polysaccharide/starch complexes combined with different sugars (trehalose, glucose, sucrose and lactose) were investigated by Fourier transform infrared spectroscopy (FT‐IR), X‐ray diffraction (XRD), scanning electron microscopy (SEM), texture profile analysis (TPA), rapid viscometer analysis (RVA) and differential scanning calorimetry (DSC). SEM showed that the complex gel systems with various sugars exhibited smoother lamellar surfaces and profiles than those of the control group after refrigeration. RVA and DSC demonstrated that the addition of sugars significantly affected the pasting of the composite gel system. TPA, FT‐IR, XRD and SEM revealed that glucose, sucrose and lactose effectively inhibited the retrogradation of the composite gel system and that glucose was a candidate for inhibition of the retrogradation of the complex gel system. Additionally, the water separation of the composite gel system with sugars was lower than that of the control group after five cycles of alternating freezing and thawing, indicating that the sugars improved the freeze‐thaw stability of the composite gel system. These results provide a theoretical direction for the use of additives in the retrogradation of starchy foods containing multiple components. The pasting and retrogradation behaviours of Mesona chinensis polysaccharide/starch complexes combined with trehalose, glucose, sucrose and lactose were investigated. These results demonstrated that glucose, sucrose and lactose effectively inhibited retrogradation of the Mesona chinensis polysaccharide/starch complexes, and glucose was a candidate for inhibiting retrogradation of the Mesona chinensis polysaccharide/starch complexes.